Complications, Reoperations, and Nutrient Deficiencies Two Years after Sleeve Gastrectomy. (21st May 2012) - Pech, Nicole; Meyer, Frank; Lippert, Hans; Manger, Thomas; Stroh, Christine
Abstract : Background . The aim of this study was to investigate patient outcomes and nutritional deficiencies following sleeve gastrectomy (SG) during a follow-up of two years. Methods . Over a period of 56 months, all consecutive patients who underwent SG were documented in this prospective, single-center, observational study. The study endpoints included operative time, complication rates, nutritional deficiencies and percentage of excess weight loss (%EWL). Results . From September 26, 2005 to May 28, 2009, 82 patients (female : male = 48 : 34) with a mean age of 43.3 years (range: 22–64) and a preoperative BMI of 52.5 kg/m² (range: 36.8–77.0) underwent SG. Major complications were observed in 9.8% of the patients, with 1 death. During follow up 51.2% of patients were supplemented with iron, 36.6% with zinc, 37.8% with calcium, 26.8% with vitamin D, 46.3% with vitamin B12 and 41.5% with folic acid. %EWL was 54.3, 65.3 and 62.6% after 6, 12 and 24 months. Conclusion . SG as a single step procedure is an effective bariatric intervention. Nutritional deficiencies after SG can be detected by routine nutritional screening. Our results show that Vitamin B12 supplementation should suggest routinely after SG.